Game Changers: National Referendums and the Politicization of Europe - Swen Hutter (Politics and Governance, 2025)
How do national referendums shape political contestation? This article explores this question by examining the politicization of European integration, a key “cleavage issue” restructuring political conflict across Europe. While national referendums are often assumed to intensify public contestation over European integration, systematic comparative evidence remains limited. This study contributes to the debate by analyzing 87 public debates on European integration across six Western European countries (Austria, Britain, France, Germany, Sweden, and Switzerland), including 12 debates with national referendums. The analysis draws on the PolDem dataset (Hutter et al., 2016), updated to include the Brexit referendum. Through comprehensive across-debate and within-debate analyses, the findings show that referendums are associated with heightened politicization, particularly by expanding actor participation and increasing issue salience. Civil society and other non-executive actors gain visibility in referendum contexts, reinforcing the view that referendums level the political playing field. Although referendums increase framing diversity, they do not consistently lead to more polarized or identity-focused debates involving radical parties, challenging the notion that referendums inherently drive cultural conflict. This study advances our understanding of how direct democracy shapes European integration debates and calls for further comparative research on institutional factors and endogenous conflict dynamics to better grasp the varied impacts of referendums on politicization.
Keywords: 320; direct democracy; European integration; framing; post-functionalism; referendums